Automation in vitrification and thawing of mouse oocytes and embryos - Zhu, Yan; Zhang, Quan-Jun; Feng, Huai L.; Luo, Jin; Miao, Shu; Jiang, Man-Xi (Frontiers in Cell and Developmental Biology, 2023)
Vitrification is a common technique for cryopreserving oocytes or embryos. However, manual vitrification is tedious and labor-intensive, and can be subject to variations caused by human factors. To address these challenges, we developed an automated vitrification-thawing system (AVTS) based on a cryo-handle. Our study firstly assessed the efficiency of cryoprotectant exchange through comparing the osmolalities of fresh and collected solutions during automated vitrification and thawing, and evaluated the cooling and warming rates of the cryo-handle. We also compared mouse oocyte survival, fertilization and embryo development after thawing and ICSI, and the development of re-frozen cleavage embryos between manual operation and automated system. The results showed that the osmolalities of collected samples were within normal range and comparable to fresh solutions. Furthermore, the automated system could obtain the reliable cooling and warming rates. Particularly, there were no significant differences in oocyte survival rates, fertilization rates, and subsequent embryo development and its quality between two procedures. Our findings suggest that AVTS has no impact on osmolalities of vitrification and thawing solutions, ensuring the proper exchange of cryoprotectants. The cryo-handle also shows the ability to achieve reliable cooling and warming rates, which benefits for the cryopreservation and thawing process. Moreover, the results from mouse oocytes and embryos indicate that automated system has effectively maintained the survival and fertilization of frozen oocytes and supported subsequent embryo development. Therefore, the automated vitrification and thawing system will inevitably represent a superior alternative to manual operation.